Perancangan Video Animasi Tentang Proses Pengembangan Video Game - Antony Antony; Tony Wibowo (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
The process of developing video game is not an easy task. Mistakes often occur due to lack of understanding within the development subject itself. This research is aimed to inform audience interested in the process of creating video game from the beginning to its completion using animated video through Moho Studio. With MDLC method, we have yielded result in a form of animated video detailing the steps of developing video game. The result has notable effect on improving the knowledge of readers or audience with interest in video game development.